The function of the endocannabinoid system in the pancreatic islet and its implications on metabolic syndrome and diabetes. Issue 1 (31st December 2023) - Cortes-Justo, Edgardo; Garfias-Ramírez, Sergio H; Vilches-Flores, Alonso
ABSTRACT: The following review focuses on the scientific studies related to the role of endocannabinoid system (ECS) in pancreatic islet physiology and dysfunction. Different natural or synthetic agonists and antagonists have been suggested as an alternative treatment for diabetes, obesity and metabolic syndrome. Therapeutic use of Cannabis led to the discovery and characterization of the ECS, a signaling complex involved in regulation of various physiological processes, including food intake and metabolism. After the development of different agonists and antagonists, evidence have demonstrated the presence and activity of cannabinoid receptors in several organs and tissues, including pancreatic islets. Insulin and glucagon expression, stimulated secretion, and the development of diabetes and other metabolic disorders have been associated with the activity and modulation of ECS in pancreatic islets. However, according to the animal model and experimental design, either endogenous or pharmacological ligands of cannabinoid receptors have guided to contradictory and paradoxical results that suggest a complex physiological interaction. In consensus, ECS activity modulates insulin and glucagon secretions according to glucose in media; over-stimulation of cannabinoid receptors affects islets negatively, leading to glucose intolerance, meanwhile the treatment with antagonists in diabetic models and humans suggests an improvement in islets function. Graphical Abstract: uf0001